Endocytic Adaptor Protein HIP1R Controls Intracellular Trafficking of Epidermal Growth Factor Receptor in Neuronal Dendritic Development - Yang, Qian; Peng, Lin; Wu, Yu; Li, Yanan; Wang, Ling; Luo, Jian-hong; Xu, Junyu (Frontiers in Molecular Neuroscience, 2018)
Huntington-interacting protein 1-related protein (HIP1R) was identified on the basis of its structural homology with Huntingtin-interacting protein 1 (HIP1). Based on its domain structure, HIP1R is a putative endocytosis-related protein. Our previous study had shown that knockdown of HIP1R induces a dramatic decrease of dendritic growth and branching in cultured rat hippocampal neurons. However, the underlying mechanism remains elucidative. In this study, we found that knockdown of HIP1R impaired the endocytosis of activated EGFR and the consequent activation of the downstream ERK and Akt proteins. Meanwhile, it blocked the epidermal growth factor (EGF)-induced neurite outgrowth. We also showed that the HIP1R fragment, amino acids 633-822 (HIP1R633-822), interacted with EGFR, and revealed a dominant negative effect in disrupting the HIP1R-EGFR interaction-mediated neuronal development. Collectively, these results reveal a novel mechanism that HIP1R plays a critical role in neurite initiation and dendritic branching in cultured hippocampal neurons via mediating the endocytosis of EGFR and downstream signaling.